Heart of the matter dealing with cardiac deaths / Sazzli Shahlan Kasim - Kasim, Sazzli Shahlan (UiTM Press, 2023)
To those who have lost their loved ones to sudden cardiac death and are looking for answers, this book is for you. It may help you grieve as you understand why things happened. It may reconcile matters among families and friends. It may help give you ideas of how to reduce your own risk and lead a healthier, happier, and long life. Come and join me and others who are now better equipped with knowledge of cardiac diseases, and together, we may just be able to make a major difference to another person's life. Do enjoy this book as I take you through my journey as a heart specialist.